EFFECTIVENESS OF FOOT REFLEXOLOGY VS BACK MASSAGE ON QUALITY OF SLEEP AMONG POST CESAREAN MOTHERS - MANJURI.A.E MSC (N),; DR. FATHIMA LATHEEF MSC (N), Ph.D, (International Journal of Pharma and Bio Sciences, 2016)
This study was intended to evaluate the effectiveness of the foot reflexology, back massage in improving the quality of sleep among the post cesarean mothers. The quality of sleep was assessed on 30 post cesarean mothers with 10 samples in each group of control, foot reflexology and back massage. The quality of sleep was assessed using the Modified Pittsburg Sleep Quality Index Scale. After the pretest, foot reflexology and back massage was given for three consecutive days in the evening for the respective mothers. In the pretest the quality of sleep was less in all the three groups. The results revealed that the post test mean score of quality of sleep of foot reflexology group 15.24(SD 3.01) was lower than of a back massage group 27.14 (SD 4.52) and control group 50.95(SD 4.52). The effect of foot reflexology and the back massage on the quality of sleep was statistically significant at p<0.001. Though, both the therapies were effective, the foot reflexology was found to be more effective than the back massage in improving the quality of sleep which is vital in healing the body and to promote the wellbeing of the mother.